My country, white or wrong: Christian nationalism, race, and blind patriotism. Issue 7 (19th May 2023) - Perry, Samuel L.; Schleifer, Cyrus
ABSTRACT: A principal concern regarding nationalist sentiment is the tendency to sanctify "the nation" and support it as chosen and pure regardless of its complicity in injustice. Building on research showing the tendency to whitewash America's past is primarily localized to white Americans, and particularly those who stress its Christian heritage, we theorize Christian nationalism amplifies Americans' willingness to endorse "blind patriotism" (supporting the nation even in the wrong), but only for white Americans as opposed to Blacks or Hispanics. General Social Survey data affirm the more Americans conflate Christian and American identities, the more they agree citizens should support their country even if it is wrong. As anticipated, this association is pronounced for white Americans, but virtually non-existent among Blacks and Hispanics. Stemming from American religious and national identities being deeply racialized, conflating the two sanctifies "the nation" but only among whites, whose national membership and hegemony were historically assumed.